Three Pillars Partnership in The Tourism Destinations Management in Order to Actualize Good Tourism Governance (Study on a Rafting Tour in Probolinggo Regency) - Indah Mindarti, Lely; Lazuardi, Muhammad Fahmi (Graduate School, Universitas Brawijaya, 2019)
Three pillars partnership in the tourism destinations management in order to actualize Good Tourism Governance has been studied with a special case on a rafting tour in Probolinggo Regency. In tourism development, the synergy of the three pillars (state, private companies, and society) is necessary. Probolinggo Regency Government in the management of the rafting tour services conducts a partnership with private sectors and society. According to the objectives of the study that have been set, the type of this research is descriptive research with a qualitative approach. In data collection, the data were collected from observations, interviews, and documents of agreement. The method of data analysis used the analysis of Miles and Huberman. The result of this research showed that Probolinggo Regency Government has conducted a partnership with the private companies and the society in managing the tourism destinations. In this case, the three pillars have their responsibility to manage the rafting tour. However, the partnership of those three pillars has to be conducted continuously to actualize Good Tourism Governance.Keywords: Good tourism governance, Partnership, Three pillars, Tourism